COVID-19-related national re-confinement: recommendations from the national french observatory for physical activity and sedentary behaviors (ONAPS) - Thivel, D.; Tardieu, M.; Genin, P.; Fillon, A.; Larras, B.; Melsens, P.; Bois, J.; Dutheil, F.; Carré, F.; Ninot, G.; Toussaint, J.-F.; Rivière, D.; et al. (Journal of Physical Activity and Health, 2021)
While a declined physical activity level (PAL) and an increase of sedentary behaviors at all ages during the COVID-19-induced first confinement period have been unanimously observed worldwide, the lately instituted new social distancing strategies and lockdowns around the world require the formulation and dissemination of adapted and accessible recommendations to promote physical activity (PA) and limit the progression of sedentary time (SED) in the upcoming weeks. From a public health perspective, it appears imperative to encourage the adoption of healthy movement behaviors despite the new activity restrictions imposed by governments to slow down the alarming progression of the SARS-CoV-2 pandemic.